The Long-Term Effects of Neonatal Inflammatory Pain on Cognitive Function and Stress Hormones Depend on the Heterogeneity of the Adolescent Period of Development in Male and Female Rats - Butkevich, Irina P.; Mikhailenko, Viktor A.; Vershinina, Elena A.; Barr, Gordon A. (Frontiers in Behavioral Neuroscience, 2021)
Exposure to stress at an early age programs the HPA axis which can lead to cognitive deficits in adults. However, it is not known whether these deficits emerge in adulthood or are expressed earlier in life. The aims of the study were to investigate 1) the immediate effects of early injury-induced stress in one-day-old (P1) and repeated stress on at P1 and P2 rat pups on plasma corticosterone levels; and 2) examine the subsequent long-term effects of this early stress on spatial learning and memory, and stress reactivity in early P26-34 and late P45-53 adolescent male and female rats. Intra-plantar injection of formalin induced prolonged and elevated levels of corticosterone in pups and impaired spatial learning and short- and long-term memory in late adolescent males and long-term memory in early adolescent females. There were sex differences in late adolescence in both learning and short-term memory. Performance on the long-term memory task was better than that on the short-term memory task for all early adolescent male and female control and stressed animals. Short-term memory was better in the late age control rats of both sexes and for formalin treated females as compared with the early age rats. These results are consistent with an impaired function of structures involved in memory (the hippocampus, amygdala, prefrontal cortex) after newborn pain. However, activation of the HPA axis by neonatal pain did not directly correlate with spatial learning and memory outcomes and the consequences of neonatal pain remain are likely multi-determined.